PENGARUH KADAR FILLER ABU BATU TERHADAP FLEKSIBILITAS PADA CAMPURAN ASPAL BETON HRS-BASE (KECAMATAN WAIGETE, KABUPATEN SIKKA) - Abdul Jabbar Adhim Husada; Yono Putra; Dedi Imanuel Pau (SIARTEK - Jurnal Teknik Sipil dan Arsitektur, 2025)
Road construction carried out today is faced with improving quality and saving construction costs. The development of research on road pavement construction materials, especially flexible pavement, is directed at efforts to utilize local materials and is adapted to the conditions of the area where the paving construction will be carried out. To determine how much influence the HRS-Base asphalt concrete mixture using rock ash filler has on the optimum asphalt content value. To obtain optimal mixture variations in achieving VIM value stability at asphalt content of 5.5% 83.99%, 6.0% 79.03%, 6.5% 78.20%. From this test, it can be said that concrete with a VIM value ≤ 3% will increase the possibility of bleeding. Due to the high temperature, the asphalt in the mixture will melt so that when the pavement receives a load, the asphalt will flow between the aggregate cavities. Conversely, if the VIM value ≥ 5% indicates that the cavities in the mixture are large, so that the mixture is not tight and not airtight to air and water, so that the asphalt is easily oxidized, which results in weakening the asphalt bond to the aggregate, and then the asphalt is unable to bind the aggregate. 70 5. In the Marshall test at the Civil Engineering Laboratory of Nusa Nipa University, the MQ value at asphalt content of 5.5% 3,690 kg/mm, 6.0% 102 kg/mm, and 6.5% 5,867 kg/mm. Based on the results of research and analysis that have been carried out to determine the extent of influence the HRS-Base asphalt concrete mixture using rock ash filler has on the optimum asphalt content value.